TRADISI YANG BERKEMBANG DI SEPUTAR SITUS CANDI PETIRTAAN CABEAN KUNTI - Hari Lelono (Berkala Arkeologi, 2003)
The slopes of Mount Merapi and Merbabu seem to be places that have always been busy since ancient times. In the Boyolali area on the eastern slopes of Mount Merapi, we can find many petirtaan/ water castles, including the Cabean Kunti / Sumur Pitu site. The tradition that is still alive is the Nguras Lepen tradition which is carried out en masse by all residents of Cabean Kunti Village, and the Ngirim Lepen tradition which is carried out by individuals. The two traditions that are still alive are both addressed to the ruler of the universe / God Almighty for the grace given in the form of water which gives life to all villagers.